Sport Aerodynamics - Noerstrud, Helge; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2008)
In sport disciplines such as running, ice skating, bicycling and cross-country skiing the aerodynamic drag force constitutes the major obstacle to overcome. Furthermore, in ski jumping and in various activities involving a ball the aerodynamic lift force comes in addition into action. This book describes the various sport disciplines on the basis of aerodynamic analysis and also cover the biomechanics part by illustrative performance examples. Such treatment of the underlying physical phenomena of sport activities gives a valuable supplement to existing literature on sport. The reader will also be guided to references which exist for the various topics discussed, so she or he can go into a deeper study of the particular sport activity at wish.
Basic Aerodynamics -- Factors influencing on running -- Cycling Aerodynamics -- Performance factors in bicycling: Human power, drag, and rolling resistance -- Skin Suit Aerodynamics in Speed Skating -- Cross-Country Skiing -- Alpine Downhill and Speed-Skiing -- Performance factors in ski jumping -- Computer simulation of ski jumping based on wind tunnel data -- Ski-Jumping Aerodynamics: Model-Experiments and CFD-Simulations -- Some Aspects of Ski Jumping -- Sports Ball Aerodynamics.
Keywords: Biomedical engineering; Fluid mechanics; Engineering; Biomedical Engineering and Bioengineering; Engineering Fluid Dynamics; Engineering, general